Features of Railway Security Design - Pirnazarov, Gulomjon; Khudjaev, Mukhiddin; Abduazimova, Iroda; Khojakhmatov, Sunnat (European Journal of Life Safety and Stability (2660-9630), 2023)
The article addresses the issues of reducing the negative impact and proposes practical measures for the design of the system to protect the railroads from sand. The absence of a logically interconnected protection system was revealed. There is an urgent need to develop theoretical and practical foundations, the practical application of which is the methodology for its design, based on constructive solutions and their organizational and technological schemes for protecting railroads from drifting sand. The research methods are the axiomatic rules for designing measures to protect railroads from quick sands.